(untitled) (KULT_online, 2021)
The essay anthology Undienlichkeit, written by Iris Därmann, assembles a history of violence and slavery. The book intersects European philosophies of subservience and forms of passive resistance, drawing special attention to spaces of violence by means of philosophical theories, historical, literary, and visual sources and a special focus on material cultures. It traverses a broad length of contexts, from slavery in ancient Greece to Auschwitz.